Reversible Image Authentication Method Based on Pre-ordered IPVO - Yang, Chang; Zhang, Zhengwei; Yue, Hao (International Journal of Computer Science and Information Technology, 2024)
To enhance the tampering accuracy of current reversible image authentication methods, we propose a novel algorithm based on pre-sorting-IPVO. The process begins by dividing the image into 2×2 blocks organized in a black and white checkerboard pattern and further categorizing them into smooth and textured blocks based on image characteristics to generate an authentication watermark. In smooth blocks, the pre-sorting-IPVO method is applied to pre-sort pixel values, prioritizing larger pixel values. Authentication watermarks are embedded in the textured blocks using the difference expansion method. Experimental results demonstrate that this algorithm effectively leverages pixel correlation to improve tampering accuracy, maintaining high detection accuracy across various conditions. It is capable of authenticating images with both smooth and complex textures.